Ablation of the calpain-targeted site in cardiac myosin binding protein-C is cardioprotective during ischemia-reperfusion injury. (April 2019) - Barefield, David Y.; McNamara, James W.; Lynch, Thomas L.; Kuster, Diederik W.D.; Govindan, Suresh; Haar, Lauren; Wang, Yang; Taylor, Erik N.; Lorenz, John N.; Nieman, Michelle L.; Zhu, Guangshuo; Luther, Pradeep K.; et al.
Abstract: Cardiac myosin binding protein-C (cMyBP-C) phosphorylation is essential for normal heart function and protects the heart from ischemia-reperfusion (I/R) injury. It is known that protein kinase-A (PKA)-mediated phosphorylation of cMyBP-C prevents I/R-dependent proteolysis, whereas dephosphorylation of cMyBP-C at PKA sites correlates with its degradation. While sites on cMyBP-C associated with phosphorylation and proteolysis co-localize, the mechanisms that link cMyBP-C phosphorylation and proteolysis during cardioprotection are not well understood. Therefore, we aimed to determine if abrogation of cMyBP-C proteolysis in association with calpain, a calcium-activated protease, confers cardioprotection during I/R injury. Calpain is activated in both human ischemic heart samples and ischemic mouse myocardium where cMyBP-C is dephosphorylated and undergoes proteolysis. Moreover, cMyBP-C is a substrate for calpain proteolysis and cleaved by calpain at residues 272-TSLAGAGRR-280, a domain termed as the calpain-target site (CTS). Cardiac-specific transgenic (Tg) mice in which the CTS motif was ablated were bred into a cMyBP-C null background. These Tg mice were conclusively shown to possess a normal basal structure and function by analysis of histology, electron microscopy, immunofluorescence microscopy, Q-space MRI of tissue architecture, echocardiography, and hemodynamics. However, the genetic ablation of the CTS motif conferred resistance to calpain-mediated proteolysis of cMyBP-C. Following I/R injury, the loss of the CTS reduced infarct size compared to non-transgenic controls. Collectively, these findings demonstrate the physiological significance of calpain-targeted cMyBP-C proteolysis and provide a rationale for studying inhibition of calpain-mediated proteolysis of cMyBP-C as a therapeutic target for cardioprotection. Highlights: Calpain-mediated proteolysis of cMyBP-C occurs in human and mouse ischemic injury. In silico analysis shows that calpain targets cMyBP-C residues 272-TSLAGAGRR-280. Loss of the calpain target site (CTS) prevents calpain-mediated cMyBP-C proteolysis. Mice expressing cMyBP-C with no CTS have normal cardiac function. Loss of the CTS is sufficient for cardioprotection in I/R injury.